The Implementation of Interactive Learning Media in Improving Students’ Learning Enthusiasm in Economics Learning - Santi Ismail Uwange; Meyko Panigoro; ⁠Risca Marsanti Halid; Frahmawati Bumulo; Fatmawaty Damiti (LPPM Universitas PGRI Semarang, 2026)
The low level of students ' learning spirit in economic learning is the main problem in this study. Students tend to show low participation during class discussions and learning activities due to monotonous teaching methods, boredom during lessons, and limited comprehension of learning materials. Therefore, the use of Interactive Learning media is considered necessary to create a more active, interesting, and student-centered learning process. This study aims to improve students ' learning spirit in economic subjects through the application of Interactive Learning Media. This study used a Class Action Research (CAR) design conducted in two cycles. The subjects of this study were students of Class XI IPS 4 and XI IPS 5 SMA Negeri 1 Telaga Biru totaling 66 students. Data collection techniques include observation, student learning enthusiasm sheet, teacher activity observation sheet, and student activity observation sheet. The results showed that the application of Interactive Learning Media successfully improve students ' learning spirit. In the first cycle, IP Class XI 4 reached 66.90%, while IP Class XI 5 reached 70.21%. In the second cycle, the score increased significantly to 83.41% for IP XI Grade 4 and 83.46% for IP XI Grade 5, both categorized as high. Therefore, it can be concluded that Interactive Learning Media successfully improved students’ learning enthusiasm in economics learning.